Demos as Grundnorm. Self-determination, Right to Decide and Democratic Constitution - Bengoetxea, Joxerramon (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
This contribution engages a conversation with Josep Maria Vilajosana’s reference text on democracy and the right to decide, and makes some theoretical proposals favoring the right to self-determination in the peaceful solution of territorial sovereignty conflicts, such as can be found in Spain regrading Catalonia and the Basque Country. It advocates a constitutional pluralist concept of demoicracy and recovers the centrality of self-determination of peoples as the self-assertion of a political community that has been systematically denied the freedom to decide on its own status and its self-definition as a people, a demos. The deep justification of self-determination lies in democracy and the right to decide and in the close links between popular sovereignty, democracy and law (justice).
Keywords: self-determination; right to decide; demos; democratic constitution; constitutional culture in Spain; territorial conflicts over sovereignty; European Union